Nutritive value of sunflower seed for swine - Laudert, S.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sunflower seed (SFS) was evaluated as a feedstuff for growing and finishing swine. In all trials, SFS was added on an isolysine basis: 10 parts SFS replacing 8 parts corn and 2 parts soybean meal. Replacement levels were 20, 40, and 60% in the growth and the digestion trials, 25 and 50% in the finishing trial. Feed intake of growing pigs decreased linearly as the level of SFS in their diets increased. At 20 and 60% levels, effect on daily gain was not significant, but at 40% replacement weight gain decreased. Ether extract digestibility increased and energy digestibility decreased as the level of SFS was increased. Apparent digestibility of SFS was determined to be: dry mattter, 69±4%; energy, 77±5%; ether extract, 91±3%; and protein, 79±5%. Average daily gain was significantly higher for finishing pigs fed the control diet than for those fed either 25 or 50% SFS, but for all diets feed required per unit of gain was similar. Increasing the level of SFS in the diet increased the total unsaturation of the lipid of backfat and longissimus dorsi. The most dramatic change was the increase of linoleic acid (from 14.7% to 34.0% to 40.5% for backfat and 9.0% to 25.3% to 32.1% for longissimus dorsi samples, respectively, for pigs fed the control, 25%, and 50% SFS diets). Backfat thickness did not differ significantly among treatments, but the trend was toward increasing amounts of intramuscular fat as SFS in the diet was increased.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Nutritional value; Sunflower seed; Digestibility